CARDIOPROTECTIVE ACTIVITY OF ETHANOLIC EXTRACT OF CITRUS GRANDIS (L.) OSBECK PEEL ON DOXORUBICIN AND CYCLOPHOSPHAMIDE INDUCED CARDIOTOXICITY IN ALBINO RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The present study was designed to evaluate the cardioprotective potential of Citrus grandis (L.) Osbeck (CGO) peel extract in rats. Citrus grandis (L.) Osbeck peel extract was evaluated for protection against cyclophosphamide (200 mg/kg body wt., i.p.) and doxorubicin (15 mg/kg body wt., i.p.) induced cardiotoxicity in male albino rats. Biomarkers like lactate dehydrogenase (LDH), alanine aminotransaminase (ALT), aspartate aminotransaminase (AST), alkaline phosphatase (ALP), total cholesterol (TC), triglyceride (TG) and creatinine kinase (CK-MB) along with heart weight index and antioxidant enzymes was considered to determine the cardioprotective property. Histopathological study was also carried out on heart of experimental animals. The CGO peel extract was found to contain alkaloids, flavonoids, steroids and triterpenoids, saponins, phenolic compounds and tannin as chemical constituents. Cyclophosphamide (CYP) and doxorubicin (DOX) treated groups exhibited significant increase in LDH, ALT, AST, ALP, TC, TG and CK-MB level and decrease in catalase (CAT), superoxide dimutase (SOD) when compared to control group. Pretreatment with different doses of CGO significantly reduced the serum biomarkers and increased the tissue antioxidant level when compared to DOX and CYP alone treated groups. Moreover, treatment with CGO also improved CYP induced changes in histopathology of heart which may be due to its antioxidant property. The Citrus grandis (L.) Osbeck exerted protective effect against CYP and DOX induced cardiotoxicity in rats, which may be due its lipid lowering and antioxidant properties. These findings might be helpful to understand the beneficial effects of CGO extract against myocardial injury although further study is needed to confirm its mechanism.